AB0698 REAL CLINICAL PRACTICE IN THE CONTROL OF REPORTED OUTCOMES BY THE PATIENT (PROS) DIAGNOSED WITH PSORIATIC ARTHRITIS AND/OR ANKYLOSING SPONDYLITIS WHO BEGIN TREATMENT WITH SECUKINUMAB. A PROSPECTIVE MULTICENTRIC STUDY. (2nd June 2020) - Lerma, J. J.; Gracia, A.; Perez, A.; Rueda, A.; Molina, C.; Pastor, M. D.; Balaguer Trull, I.; Valiente, I.; Campos Fernández, C.; Calvo, J.; Carmona, L.
Abstract : Background: Objectives: Analyse the effect of secukinumab in terms of the patient´s own variables, specifically: fatigue, sleep, pain and quality of life in patients with psoriatic arthritis or spondyloarthritis. Methods: A multicentric longtitudinal observational prospective study was carried out at 6 months in patients who begin treatment with secukinumab. At the start and after 6 months the following data was collected on the outcome: pain through an visual analogue scale (VAS), fatigue using the FACIT-fatigue scale, sleeping problems using the insomnia severity index (ISI) and quality of life with the EuroQol-3L-5D and the PsAQoL. The sample can be described in terms of the distribution of the variables through measures of central tendency.It was analysed if the change after 6 months was statistically relevant using Student´s t-test for paired data in the case of FACIT, VAS, PsAQoL and ISI and chi-squared for the dimensions of the EQ-5D. The size of the effect of each of the measurements taken was calculated using Cohen's D. the results are given grouped by disease and globally. The analysis was carried out using Stata v12 (College Station Tx, USA) Results: In table 1, the changes in the scales of normal distribution can be seen. Apart from general VAS, all the scales experience significant relevant changes. The PROs preferred by the patient with the best therapeutic response is the quality of sleep. The adjustment of the regression models does not produce changes in the results, apart from small adjustments to the condidence intervals (final column table 1). The subdomain in which the most significant change in the EQ-5D is produced is in that of pain and discomfort. Conclusion: After 6 months patients who begin treatment with secukinumab, present with improvements in all sizes of the effects of the treatment in the various studied scales. The improvement achieves global and generalised statistical significance after 6 months of study. The greatest effect is on sleep, quality of life and fatigue. The measurements of the outcomes reported by the patients are a clinical value added to our objective evaluations of the health and activity of the disease, and allow us, in a more integrated and comprehensive manner, to undertake a more exact and close evaluation of their state of health and wellbeing. Disclosure of Interests: JUAN JOSE LERMA: None declared, Antonio Gracia: None declared, Antonio Perez: None declared, Amalia Rueda: None declared, Clara Molina: None declared, M. Dolores Pastor: None declared, Isabel Balaguer Trull: None declared, Inmaculada Valiente: None declared, Cristina Campos Fernández: None declared, Javier Calvo: None declared, Loreto Carmona Grant/research support from: Novartis Farmaceutica, SA, Pfizer, S.L.U., Merck Sharp & Dohme España, S.A., Roche Farma, S.A, Sanofi Aventis, AbbVie Spain, S.L.U., and Laboratorios Gebro Pharma, SA (All trhough institution)